2022
DOI: 10.3390/cells11081358
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Proteasome System and Microtubules Are Master Regulators of Central and Peripheral Nervous System Axon Degeneration

Abstract: Axonal degeneration is an active process that differs from neuronal death, and it is the hallmark of many disorders affecting the central and peripheral nervous system. Starting from the analyses of Wallerian degeneration, the simplest experimental model, here we describe how the long projecting neuronal populations affected in Parkinson’s disease and chemotherapy-induced peripheral neuropathies share commonalities in the mechanisms and molecular players driving the earliest phase of axon degeneration. Indeed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…CD36 induced accumulation of lipids in peripheral nerves may indeed overwhelm the capacity of SCs and axons to metabolize these compounds through mitochondrial β-oxidation, the TCA cycle and oxidative phosphorylation to generate ATP. We also found that proteins involved in proteasomal catabolic processes and microtubule biology were downregulated, both parameters being indicative of neurodegenerative processes (40, 41). Furthermore, we found structurally abnormal and dysfunctional mitochondria within unmyelinated Remak bundle fibers of PCSK9 deficient mice.…”
Section: Discussionmentioning
confidence: 70%
“…CD36 induced accumulation of lipids in peripheral nerves may indeed overwhelm the capacity of SCs and axons to metabolize these compounds through mitochondrial β-oxidation, the TCA cycle and oxidative phosphorylation to generate ATP. We also found that proteins involved in proteasomal catabolic processes and microtubule biology were downregulated, both parameters being indicative of neurodegenerative processes (40, 41). Furthermore, we found structurally abnormal and dysfunctional mitochondria within unmyelinated Remak bundle fibers of PCSK9 deficient mice.…”
Section: Discussionmentioning
confidence: 70%
“… 81 , 84 , 85 Our integrative miRNA–mRNA profiling identified NEDD4 as a potentially important player in the epidermal microenvironment. NEDD4 is known to participate in the regulation of axonal growth, neuronal hyperexcitability 63 , 86 and Nav1.7 modulation. 63 , 87-89 To investigate its effect on Nav1.7, which has been previously proposed as a potential biomarker for painful neuropathy, 90 we performed IFA in skin biopsy sections from 11 NavNP patients carrying W1538R, L1267V, D1908G and/or V991L/M932L haplotypes and in 18 HC ( Supplementary Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that potassium channels play a role in the hyperexcitability of peripheral neuropathy [27,28], and bortezomib has been shown to affect microtubule polymerization and axonal transport in rat DRG neurons [29]. U The ubiquitin proteasome system and microtubules are recognized as master regulators of central and peripheral nervous system axon degeneration [30]. Furthermore, mitochondrial damage and oxidative stress are well-documented events in CIPN [8,31].…”
Section: Gene Interaction Analysis Unveiled Gene Modules Associated W...mentioning
confidence: 99%